MOLECULAR IDENTIFICATION OF ROSEOMONAS MUCOSA AND DETERMINATION THE SOME OF ITS VIRULENCE FACTORS - Teeba G. Albadri; Mouruj A. Alaubydi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to characterize Roseomonas mucosa isolate using molecular genetics and determination some bacterial virulence factors such as capsular, biofilm formation and antimicrobial susceptibility. By using Polymerase chain reaction (PCR) technique, the molecular characterization of the R. mucosa was done by using 16S rRNA gene sequence and phylogenetic analysis. Antimicrobial susceptibility test was carried out by Kirby-Bauer disk diffusion method. Capsular detection was examined using nigrosin pigment. While Congo red agar and microtiter plate using enzyme-linked immunosorbent assay (ELISA) reader methods are used to determined bacterial isolate capability to produce a biofilm. The molecular characterization shows the bacterium that isolated from catheter of a dialysis Iraqi patient is belong to Roseomonas mucosa. The isolated R. mucosa strain showed resistant to Amoxicillin, methicillin, carbapenemes, bacitracin and Sulfamethoxazole. While it was susceptible to tobramycin, levofloxacin, colisitin sulphate, doxycycline, azithromycin and cephalexin. The results show R. mucosa was encapsulated. Furthermore, it has the ability to form weak biofilm. The findings suggest that in spite of this genus seems to have an overall little pathogenic potential for humans, Roseomonas sp. in particular, R. mucosa may be substantial pathogens in individuals with underlying medical complications.